Longitudinal assessment of COVID-19 vaccine immunogenicity in people with HIV stratified by CD4+ T-cell count in the Netherlands: A two-year follow-up study - Marlou J. Jongkees; Susanne Bogers; Rory D. de Vries; Corine H. GeurtsvanKessel; Pedro Miranda Afonso; Kathryn S. Hensley; Bart J. A. Rijnders; Kees Brinkman; Casper Rokx; Anna H. E. Roukens (PLoS ONE, 2025)
Background Although guidelines for COVID-19 additional vaccination strategies generally prioritise people with advanced HIV infection, recommendations vary globally, with some countries recommending an annual vaccination for all people with HIV (PWH), while others restrict this to PWH with a CD4+ T-cell count < 200 cells per µL. Methods We conducted a prospective cohort study in 448 adult PWH. The primary outcome was the SARS-CoV-2 spike (S1)-specific IgG antibody level at 1, 6, 12, 18, and 24 months after completing a primary COVID-19 vaccination series (two doses of BNT162b2, mRNA-1273, or ChAdOx1-S, or one dose of Ad26.COV2.S). We compared the antibody kinetics over two years between PWH with a baseline CD4+ T-cell count < 200 cells per µL (n = 16) vs. ≥ 200 cells per µL (n = 432) with a mixed-effects model. Secondary outcomes included variables associated with the kinetics of S1-specific antibody levels and the incidence of breakthrough infections. Results The median most recent CD4+ T-cell count prior to primary vaccination was 140 (IQR 80–165) in the < 200 cells per µL group, and 688 (IQR 520–899) in the ≥ 200 cells per µL group at the time of primary vaccination. S1-specific antibodies were lower in PWH with a CD4+ T-cell count < 200 vs. ≥ 200 cells per µL during the two-year follow-up, with predicted S1-specific antibody levels of 514 (95% CI 456–578) vs. 2758 (95% CI 1488–5110) BAU per mL at 12 months (p < 0.001) and 839 (95% CI 732–959) vs. 3505 (95% CI 1712–7175) BAU per mL at 24 months (p < 0.001). The overall incidence of SARS-CoV-2 infections was 55% and comparable between groups. A CD4+ T-cell count < 200 cells per µL, higher age, and a vector-based primary vaccination series were negatively associated with S1-specific antibody levels over time. Conclusion Long-term humoral responses were lower in PWH with a CD4+ T-cell count < 200 cells per µL compared to those with a CD4+ T-cell count ≥ 200 cells per µL. National COVID-19 vaccine guidelines recommending booster vaccines for all PWH, should therefore specifically emphasise the need for booster vaccines in those with a CD4+ T-cell count < 200 cells per µL. Trial registration: The trial was registered on the International Clinical Trials Platform (registration number: EUCTR2021-001054-57-N).